Graphite and preparation method thereof, negative pole piece, secondary battery and energy storage device
By preparing graphite with a specific structural stability coefficient, the problem of poor structural stability of graphite after rolling is solved, and the long cycle performance and safety performance of the battery are improved.
Patent Information
- Application Number
- CN202510063774.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
The structural stability of existing graphite becomes worse after rolling, affecting the long cycle performance and safety performance of the battery.
It is provided that has a first structural stability coefficient X1 in the range of 0.90 to 1.80. Through a specific preparation method and rolling conditions, graphite still has good structural stability after rolling.
The structural stability of the graphite can match the requirements of rolling operation, ensuring that the battery has long cycle performance and safety performance.
Smart Images

Figure CN119890298A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to graphite and a preparation method thereof, a negative electrode sheet, a secondary battery, and an energy storage device. Background Art
[0002] As an important negative electrode active material, graphite has a wide range of applications in the battery field. As the market's requirements for long-cycle battery performance become increasingly higher, the particle stability of graphite has attracted people's attention. However, in the process of using graphite as a negative electrode active material to make pole pieces, the rolling operation has very high requirements for the structural stability of graphite. Therefore, it is necessary to provide a graphite with a structural stability that better matches the requirements of the rolling operation, so as to reduce the deterioration of graphite stability after rolling, the destruction of graphite structure during the cycle, and thus affect the performance of various aspects of the battery. Summary of the invention
[0003] In order to solve the above technical problems, the embodiments of the present application provide a graphite and a preparation method thereof, a negative electrode plate, a secondary battery, and an energy storage device.
[0004] In a first aspect, the present application provides a graphite having a first structural stability coefficient X1, wherein X1 is (Dv90-Dv50) / (Dv90'-Dv50'), 0.90≤X1≤1.80;
[0005] Among them, Dv90 is the particle size corresponding to 90% of the cumulative volume percentage of the graphite before rolling, Dv50 is the particle size corresponding to 50% of the cumulative volume percentage of the graphite before rolling, Dv90' is the particle size corresponding to 90% of the cumulative volume percentage of the graphite after rolling, and Dv50' is the particle size corresponding to 90% of the cumulative volume percentage of the graphite after rolling.
[0006] Furthermore, the rolling conditions include: applying a pressure of 800MPa to 1500MPa to the graphite for rolling at a rotation speed of 10m / min to 40m / min.
[0007] Furthermore, the compacted density of the graphite is 1.50 g / cm 3 ~1.90g / cm 3 .
[0008] Further, 17μm≤Dv90≤26μm.
[0009] Furthermore, 10 μm ≤ Dv50 ≤ 15.5 μm.
[0010] Furthermore, 17 μm ≤ Dv90' ≤ 25 μm.
[0011] Furthermore, 9.5 μm≤Dv50′≤15 μm.
[0012] Furthermore, the graphite also has a second structural stability coefficient X2, wherein X2 is (Dv90-Dv10) / (Dv90'-Dv10'), 0.95≤X2≤2;
[0013] Wherein, Dv10 is the particle size corresponding to 10% of the cumulative volume percentage of the graphite before rolling, and Dv10' is the particle size corresponding to 10% of the cumulative volume percentage of the graphite after rolling.
[0014] Furthermore, 5μm≤Dv10≤9.5μm.
[0015] Furthermore, 4 μm ≤ Dv10' ≤ 7.5 μm.
[0016] Furthermore, the tap density of the graphite is 1.0 g / cm 3 ~1.2g / cm 3 .
[0017] Furthermore, the specific surface area of the graphite is 1.1 m 2 / g~1.6m 2 / g.
[0018] Furthermore, the gram capacity of the graphite is 340 mAh / g to 370 mAh / g.
[0019] In a second aspect, the present application provides a method for preparing graphite as described in the first aspect, wherein the method for preparing graphite comprises the following steps:
[0020] Crushing the raw coke to obtain aggregate, wherein the aggregate has a median particle size Dv0 of 6.0 μm to 9.0 μm;
[0021] Granulating the aggregate to obtain a first material, wherein the first material has a first median particle size Dv1, 1.7≤Dv1 / Dv0≤2.6;
[0022] The first material is shaped to obtain a second material, wherein the second material has a second median particle size Dv2, 1.5≤Dv2 / Dv0≤1.8;
[0023] Pre-carbonizing the second material to obtain a third material;
[0024] Graphitizing the third material to obtain a fourth material;
[0025] The graphite is obtained by sieving.
[0026] Furthermore, Dv1 is 10.0 μm to 22.0 μm.
[0027] Furthermore, Dv2 is 11.0 μm to 16.0 μm.
[0028] Furthermore, the tap density of the second material is ≥0.5 g / cm 3 .
[0029] Furthermore, the tap density of the third material is ≥0.7 g / cm 3 .
[0030] Furthermore, the tap density of the fourth material is ≥0.8 g / cm 3 .
[0031] In a third aspect, the present application provides a negative electrode plate, the negative electrode plate comprising:
[0032] Anode current collector;
[0033] The negative electrode active material layer is disposed on at least one side of the negative electrode current collector, and the negative electrode active material layer includes the graphite as described in the first aspect, or the negative electrode active material layer includes graphite prepared by the graphite preparation method as described in the second aspect.
[0034] In a fourth aspect, the present application provides a secondary battery, comprising: a positive electrode plate, a negative electrode plate as described in the third aspect, a separator and an electrolyte, wherein the separator is arranged between the positive electrode plate and the negative electrode plate to form a battery cell, and the electrolyte is injected into the battery cell.
[0035] Furthermore, the electrolyte includes: a lithium salt, an organic solvent and an additive, the additive includes a sulfonate compound, the mass fraction of the sulfonate compound in the electrolyte is W, 0.2%≤W / X1≤1.0%.
[0036] In a fifth aspect, the present application provides an energy storage device, which includes the secondary battery as described in the fourth aspect.
[0037] Compared with the prior art, the beneficial effects of this application are as follows:
[0038] The graphite of the present application has a first structural stability coefficient X1 and satisfies the range of 0.90 to 1.80. It has a good comprehensive structural stability, can match the requirements of the rolling operation for graphite, and ensure that the graphite after rolling still has a suitable structural stability, thereby enabling the properties of the graphite to ensure that the battery has long cycle performance and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0040] Figure 1 is a structural schematic diagram of a household energy storage system according to an embodiment of the present application;
[0041] Figure 2 It is a structural schematic diagram of a commercial energy storage system according to an embodiment of the present application.
[0042] Figure numerals: 100, energy storage system; 101, household energy storage system; 102, commercial energy storage system; 10, energy storage device; 20, electric energy conversion device; 30, first user load; 40, second user load; 50, high-voltage cable; 60, first electric energy conversion device; 70, second electric energy conversion device. DETAILED DESCRIPTION
[0043] In the present invention, the directions or positional relationships indicated by the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "middle", "vertical", "horizontal", "lateral", "longitudinal" and the like are based on the directions or positional relationships shown in the drawings. These terms are mainly used to better describe the present invention and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific direction, or to be constructed and operated in a specific direction.
[0044] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those skilled in the art, the specific meanings of these terms in the present invention can be understood according to specific circumstances.
[0045] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0046] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.
[0047] The technical solution of the present invention will be further described below in conjunction with embodiments.
[0048] For secondary batteries, increasing the compaction density of active materials is beneficial to improving the battery's endurance, but this requires overcoming great difficulties during production practice.
[0049] Taking graphite, an important active material, as an example, if you want to increase the compaction density of graphite, you need to use higher and more stringent compaction conditions. However, higher compaction conditions will in turn affect the structural stability of the active material, resulting in the active material being compacted more tightly but the structure being destroyed, which in turn affects other important properties of the active material.
[0050] Although the change in the median particle size of graphite before and after powder pressing can reflect the stability of graphite before and after powder pressing to a certain extent, such graphite stability cannot well meet the stability before and after roller pressing. On the one hand, when the graphite is subjected to powder pressing, in addition to the pressure applied by the powder pressing, the graphite is in a static rather than moving state. However, when the graphite is subjected to roller pressing, in addition to the pressure applied by the roller on the graphite, the graphite will also move as the roller rotates. That is, one of the important differences between powder pressing and roller pressing is that before and after roller pressing, the influence of the combined factors of pressure and dynamic displacement on the structural stability of graphite must be considered, but before and after powder pressing, only the influence of pressure on the structural stability of graphite needs to be considered, and the stresses on graphite under the two operations are different. On the other hand, when the graphite is subjected to powder pressing, part of the stress is usually released in advance, and then the graphite is subjected to pressure. However, when the graphite is subjected to roller pressing, the stress on the graphite is not released in advance, but is directly squeezed, which also makes the roller pressing operation require higher structural stability of graphite.
[0051] It can be seen from this that the roller pressing operation has higher requirements on the structural stability of graphite. Graphite with good structural stability after powder pressing cannot be guaranteed to maintain good structural stability after roller pressing. After roller pressing, the graphite structure will still be destroyed.
[0052] Based on in-depth analysis of the above problems and creative work, the embodiments of the present application provide a graphite and a preparation method thereof, a negative electrode plate, a secondary battery, and an energy storage device. The graphite has a more suitable structural stability and can better meet the requirements of rolling operations.
[0053] In the first aspect, the embodiment of the present application provides a graphite having a first structural stability coefficient of X1, X1 being (Dv90-Dv50) / (Dv90'-Dv50'), 0.9≤X1≤1.8. Wherein, Dv90 is the particle size corresponding to 90% of the cumulative volume percentage of the graphite before rolling, Dv50 is the particle size corresponding to 50% of the cumulative volume percentage of the graphite before rolling, Dv90' is the particle size corresponding to 90% of the cumulative volume percentage of the graphite after rolling, and Dv50' is the particle size corresponding to 90% of the cumulative volume percentage of the graphite after rolling.
[0054] Graphite that meets the above-mentioned first structural stability coefficient X1 range has good comprehensive structural stability, which can match the requirements of the rolling operation for graphite, ensuring that the graphite after rolling still has a suitable structural stability, thereby making the properties of the graphite able to meet the battery's requirements for long cycle performance and ensure that the battery has good safety performance.
[0055] Among them, the first structural stability coefficient X1 is 0.9 to 1.8, indicating that the graphite does not have a large amount of structural breakage after rolling, which is conducive to ensuring that the battery composed of the pole piece using the graphite has long cycle performance, and still has a high capacity retention rate after a large number of repeated charge and discharge. It also shows that the graphite still has a certain degree of particle reduction after rolling, and the median particle size is almost unchanged due to the excessive strength of the graphite particles. It is conducive to weakening the volume expansion phenomenon of the battery composed of the pole piece using the graphite during the charging and discharging process, reducing the stress generated inside the battery, and ensuring the cycle performance and safety of the battery. In summary, since the structural stability of the graphite in the embodiment of the present application can better match the rolling operation, it can ensure good safety performance while satisfying the battery to provide longer-term cycle performance.
[0056] In particular, when the graphite includes secondary particles formed by the aggregation of primary particles, the first structural stability coefficient X1 of the graphite is 0.9-1.8, indicating that after rolling, neither a large number of graphite particle structures themselves are damaged, nor a large number of secondary particles are dispersed into more fine primary particles. Therefore, the structural rigidity and stability of the graphite before and after rolling meet the rolling requirements.
[0057] In addition, as mentioned above, compared with static powder pressing, which only needs to bear the stress caused by compression deformation, the graphite of the embodiment of the present application is in a dynamic change process when rolling, and it needs to bear the stress caused by displacement and deformation at the same time. Therefore, when the first structural stability coefficient X1 before and after rolling is between 0.9 and 1.8, the graphite has a stability that is more compatible with the rolling operation. In addition, compared with the ratio of the median particle size before and after powder pressing, the ratio of the cumulative volume percentage before and after rolling to 90% and 50% of the particle size difference can not only reflect the volume distribution width of graphite including medium and large particles, but also reflect the changes in small and medium particles of graphite, and indirectly reflect the changes in the pore structure and stacking degree of graphite particles before and after rolling. As a result, it can be more comprehensively reflected that the degree of particle change of graphite particles under the influence of the dual factors of displacement and deformation stress before and after rolling can ensure that the graphite with the first structural stability coefficient X1 in the range of 0.9 to 1.8 has a good structural comprehensive stability under rolling conditions.
[0058] It should be noted that roller pressing refers to the operation of using equipment such as a roller press to put the material between the extrusion rollers of the roller press and use pressure to extrude the material. During the roller pressing process, the material will be deformed by the extrusion roller and move with the rotation of the extrusion roller. Therefore, the material is in a dynamic process when the material is roller pressed, and the material is subjected to stresses of both deformation and displacement. In contrast, powder pressing only applies pressure to the material, during which the material is only subjected to stress of deformation and is not affected by displacement. In a comprehensive comparison, when the structural stability coefficient of graphite before and after roller pressing meets the range of the first structural stability coefficient X1 mentioned above, graphite has a comprehensive structural stability that is more suitable for roller pressing operations.
[0059] Further, the rolling conditions include: at a speed of 10m / min to 40m / min, the graphite is pressed at a pressure of 800MPa to 1500MPa. The speed of the rolling operation is 10m / min to 40m / min, including any value within the speed range, for example, the speed of the rolling operation is 10m / min, 15m / min, 20m / min, 25m / min, 30m / min, 35m / min or 40m / min. The rolling pressure is 800MPa to 1500MPa, including any value within the pressure range, for example, the rolling pressure is 800MPa, 900MPa, 1000MPa, 1200MPa, 1300MPa or 1500MPa.
[0060] Furthermore, the compacted density of graphite is 1.50 g / cm 3 ~1.90g / cm 3 Among them, the compacted density of graphite is 1.50g / cm 3 ~1.90g / cm3 Includes any point value within this numerical range, for example, the compacted density of graphite is 1.50g / cm 3 , 1.55g / cm 3 , 1.60g / cm 3 , 1.65g / cm 3 , 1.70g / cm 3 , 1.75g / cm 3 , 1.80g / cm 3 , 1.85g / cm 3 or 1.90g / cm 3 .
[0061] The above-mentioned rolling conditions belong to high-pressure conditions. Such high-pressure conditions are conducive to graphite obtaining a higher compaction density, but they also have high requirements on the structural stability of the graphite before and after rolling. Under such rolling conditions, graphite with too low structural strength is easy to break after rolling, which affects the compaction density of the graphite and also affects the service life of the pole piece during the charging and discharging process, thereby affecting the battery cycle performance; graphite with too high structural strength is prone to more obvious volume expansion, which produces greater stress inside the battery, thereby deteriorating the battery's cycle performance and safety performance. The graphite in the embodiment of the present application has a first structural stability coefficient X1 in the range of 0.9 to 1.8, which can adapt to the above-mentioned high-pressure conditions, so that when the rolled graphite is used as an active material, it is beneficial for the battery using the graphite to obtain, for example, 1.50g / cm 3 ~1.90g / cm 3 It can achieve a high level of compaction density while ensuring that the battery has good cycle performance and safety performance.
[0062] Furthermore, the graphite also has a second structural stability coefficient X2, X2 is (Dv90-Dv10) / (Dv90'-Dv10'), 0.95≤X2≤2. Wherein, Dv10 is the particle size corresponding to the cumulative volume percentage of the graphite before rolling reaching 10%, and Dv10' is the particle size corresponding to the cumulative volume percentage of the graphite after rolling reaching 10%.
[0063] When graphite has the second structural stability coefficient within the above range, it is also helpful to further improve the high temperature cycle performance of the battery composed of the pole piece using the graphite. The graphite of the embodiment of the present application satisfies both the first structural stability coefficient X1 and the second structural stability coefficient X2. Its particle structure not only has structural stability and rigidity that match the rolling operation, but also has a better gradation gradient between large particles, medium particles and small particles, so that the graphite has a suitable pore space and particle stacking degree, and the particle distribution of the graphite is better, so that it can meet both the high compaction density requirements and the cycle performance under high temperature conditions.
[0064] Further, 17μm≤Dv90≤26μm.
[0065] Furthermore, 10 μm ≤ Dv50 ≤ 15.5 μm.
[0066] Furthermore, 17 μm ≤ Dv90' ≤ 25 μm.
[0067] Furthermore, 9.5 μm≤Dv50′≤15 μm.
[0068] Furthermore, 5μm≤Dv10≤9.5μm.
[0069] Furthermore, 4 μm ≤ Dv10' ≤ 7.5 μm.
[0070] Further controlling the particle size before and after rolling within the above range is conducive to better meeting the structural stability coefficient range of X1 and X2, so that the comprehensive structural stability and high-temperature cycle performance of the graphite are better.
[0071] Furthermore, the tap density of graphite is 1.0 g / cm 3 ~1.2g / cm 3 Among them, the tap density of graphite is 1.0g / cm 3 ~1.2g / cm 3 Includes any point value within this numerical range, for example, the tap density of graphite is 1.0g / cm 3 , 1.02g / cm 3 , 1.05g / cm 3 , 1.08g / cm 3 , 1.1g / cm 3 , 1.12g / cm 3 , 1.15g / cm 3 , 1.18g / cm 3 or 1.2g / cm 3 .
[0072] Furthermore, the specific surface area of graphite is 1.1 m 2 / g~1.6m 2 / g. Among them, the specific surface area of graphite is 1.1m 2 / g~1.6m 2 / g includes any point value within this numerical range. For example, the specific surface area of graphite is 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g or 1.6m 2 / g.
[0073] Furthermore, the gram capacity of graphite is 340mAh / g to 370mAh / g. Among them, the gram capacity of graphite is 340mAh / g to 370mAh / g, including any point value within this numerical range, for example, the gram capacity of graphite is 340mAh / g, 345mAh / g, 350mAh / g, 355mAh / g, 360mAh / g, 365mAh / g or 370mAh / g. The above-mentioned gram capacity level of graphite, when applied to electrodes and assembled into batteries, is beneficial to improving the capacity level of the battery. In addition, when the compaction density of graphite is at a higher level, for example, the compaction density of graphite is 1.50g / cm 3 ~1.90g / cm 3 At the same time, the above-mentioned gram capacity level of graphite is beneficial to improve the energy density of the battery and enhance the battery life.
[0074] In a second aspect, an embodiment of the present application provides a method for preparing graphite as described in the first aspect, the method for preparing graphite comprising the following steps:
[0075] The raw coke is crushed to obtain aggregates, wherein the aggregates have a median particle size Dv0 of 6.0 μm to 9.0 μm;
[0076] Granulating the aggregate to obtain a first material, wherein the first material has a first median particle size Dv1, 1.7≤Dv1 / Dv0≤2.6;
[0077] The first material is shaped to obtain a second material, wherein the second material has a second median particle size Dv2, 1.5≤Dv2 / Dv0≤1.8;
[0078] Pre-carbonizing the second material to obtain a third material;
[0079] The third material is graphitized to obtain a fourth material, and the tap density of the fourth material is ≥0.8g / cm 3 ;
[0080] The fourth material is screened to obtain graphite.
[0081] Among them, the median particle size Dv of each material refers to the particle size corresponding to the cumulative volume percentage of the material reaching 50%. Taking the aggregate median particle size Dv0 of the aggregate as an example, Dv0 refers to the particle size corresponding to the cumulative volume percentage of the aggregate reaching 50%. Dv1 refers to the particle size corresponding to the cumulative volume percentage of the first material reaching 50%. Dv2 refers to the particle size corresponding to the cumulative volume percentage of the second material reaching 50%.
[0082] While adopting the above-mentioned process step sequence, the median particle size of the aggregate and the ratio of the median particle size of the material before and after multiple steps of processing and the tap density are controlled within the above-mentioned range, which is conducive to more accurate control of the particle size of the material obtained in each step and the structural stability of the material, so that the final graphite satisfies the first structural stability coefficient X1 in the range of 0.9 to 1.8.
[0083] Among them, by controlling the Dv0 of the crushed aggregate to 6.0μm to 9.0μm, such an aggregate median particle size can be used as a particle size benchmark, which has two main effects on subsequent operations: on the one hand, it is conducive to enhancing the self-bonding ability of the material particles and assisting in achieving a good granulation effect in the subsequent granulation step. As a result, there is no need to add excessive asphalt in the granulation step to improve the bonding property, and a third material with a suitable median particle size range and strong bonding force can be obtained, avoiding the adverse effects on the graphite processing performance and the high-temperature cycle performance of the battery due to the addition of excessive asphalt. On the other hand, it is conducive to balancing the consumption of lithium sources by graphite, avoiding the secondary particles formed after granulation from being bonded by a large number of primary particles with too small a particle size, thereby avoiding the excessive consumption of lithium sources by graphite with such structural characteristics during the battery charging and discharging process, causing the high-temperature performance of the battery to deteriorate.
[0084] On this basis, the ratio of the median particle size of the material after granulation to that before granulation is further controlled to be in the range of 1.7 to 2.6, which can achieve deep granulation of the aggregate. Compared with weak granulation, deep granulation can make the secondary particles formed by the aggregation of primary particles more bonded and more isotropic, which not only provides more directions and channels for the insertion and extraction of lithium ions, improves the energy efficiency and dynamics of graphite, but also improves the structural stability of secondary particles. Shaping is performed after granulation, and the ratio of the median particle size of the material after shaping to that before granulation is controlled in the range of 1.5 to 1.8, which can promote better structural stability of secondary particles and reduce the sharp parts of secondary particles, making the morphology of secondary particles more rounded, reducing irreversible lithium consumption in the film formation process, and is conducive to the formation of a stable SEI film, improving the overall electrical performance and safety performance of the battery cell.
[0085] In addition, the present application adopts a process sequence of granulation first and shaping later, and obtains secondary particles by granulation first, and makes them have a first median particle size of suitable size, and then shapes the secondary particles to modify their morphology, so that the shaped secondary particles are more rounded, the particle size is more uniform, there is no more fine powder, and there are few irregular shaped particles such as flakes, feathers, and corners. The sphericity of the secondary particles is also improved, which is conducive to forming a stable and dense SEI and reducing the SEI rupture-reorganization phenomenon caused by the irregular tip of graphite during the cycle. Although the aggregate obtained by crushing can also be shaped first, and the morphology can be repaired before granulation, the granulation process will cause the aggregate particles to be broken and the fine powder to increase, and the secondary particle size between the pre-carbonization steps cannot be stably controlled, or secondary shaping is still required.
[0086] Further, Dv1 is 10.0 μm to 22.0 μm. Exemplarily, Dv1 is 10.0 μm, 12.0 μm, 14.0 μm, 16.0 μm, 18.0 μm, 20.0 μm or 22.0 μm. The granulation step is to aggregate the primary particles to form secondary particles. The aggregates before granulation belong to the primary particles. The first material obtained by granulating these aggregates includes secondary particles formed by the aggregation of the aggregates. Controlling the first median particle size Dv1 of the first material within the above-mentioned particle size range is conducive to ensuring that the obtained secondary particles have good structural stability and particle size, so as to cooperate with the subsequent process steps to obtain graphite that can match the requirements of the rolling operation.
[0087] Further, Dv2 is 11.0 μm to 16.0 μm. Exemplarily, Dv2 is 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, 15.0 μm or 16.0 μm.
[0088] Furthermore, the tap density of the second material is ≥0.5 g / cm 3 For example, the tap density of the second material is 0.5 g / cm 3 , 0.55g / cm 3 、0.58g / cm 3 , 0.6g / cm 3 , 0.65g / cm 3 or 0.68g / cm 3 .
[0089] The particle size of the material does not change much or decreases slightly before and after shaping, but the overall shape is more rounded, which is beneficial to improving the tap density.
[0090] Furthermore, the tap density of the third material is ≥0.7 g / cm 3 For example, the tap density of the third material is 0.7 g / cm 3 , 0.72g / cm 3, 0.74g / cm 3 , 0.76g / cm 3 or 0.78g / cm 3 .
[0091] Furthermore, the tap density of the fourth material is ≥0.8 g / cm 3 For example, the tap density of the fourth material is 0.8 g / cm 3 , 0.82g / cm 3 , 0.84g / cm 3 , 0.86g / cm 3 or 0.88g / cm 3 .
[0092] By precisely controlling the median particle size and / or tap density of the material obtained by the above steps, it can be better ensured that the graphite finally obtained has a structural stability that matches the requirements of the rolling operation.
[0093] Furthermore, the step of crushing the raw coke to obtain aggregates includes: roughly crushing the raw coke to obtain coarse aggregates, the coarse aggregates have a coarse aggregate median particle size Dv0'; finely crushing the coarse aggregates to obtain aggregates, 2.1≤Dv0' / Dv0≤2.8, and Dv0' is 13.0μm to 25.0μm.
[0094] By first coarse crushing and then fine crushing and controlling the median particle size of the coarse material so that its ratio to the median particle size of the aggregate after fine crushing is within the above range, it is beneficial to more accurately control the acquisition of aggregates with appropriate particle sizes.
[0095] In some embodiments of the above-mentioned graphite preparation method, graphite can be prepared using the following related raw material types or process conditions.
[0096] In terms of raw materials, the raw coke in the embodiments of the present application includes at least one of petroleum coke, asphalt coke or needle coke.
[0097] In the step of crushing the raw coke to obtain aggregate, the raw coke is firstly ground for 1 hour to 5 hours to obtain coarse material, and then the coarse material is finely crushed with a power of 10 Hz to 50 Hz to obtain aggregate.
[0098] In the step of granulating the aggregate to obtain the first material, asphalt is used as an additive for granulation, the softening point of the asphalt is 200° C. to 250° C., and the addition amount of the asphalt is 0.01wt% to 5wt%.
[0099] In the step of pre-carbonizing the second material to obtain the third material, the pre-carbonization treatment temperature is 700° C. to 1500° C., and the treatment time is 8 h to 60 h.
[0100] In the step of graphitizing the third material to obtain the fourth material, the power of the graphitization treatment is ≥500kW, the temperature of the graphitization treatment is 2000°C to 3500°C, and the insulation time is 12h to 24h; the heating method of the graphitization includes: at least one of arc heating, plasma heating or resistance heating.
[0101] In a third aspect, an embodiment of the present application provides a negative electrode plate, the negative electrode plate comprising:
[0102] Anode current collector;
[0103] The negative electrode active material layer is disposed on at least one side of the negative electrode current collector, and the negative electrode active material layer includes the graphite as described in the first aspect, or the negative electrode active material layer includes the graphite prepared by the preparation method as described in the second aspect.
[0104] The negative electrode active material layer may be disposed on one or both sides of the negative electrode current collector. In addition to graphite as the negative electrode active material, the negative electrode active material layer may also include conventional amounts of binders, conductive agents, thickeners, etc. as functional additives, which are not limited in this application.
[0105] The method for preparing the negative electrode sheet comprises the following steps:
[0106] Applying the negative electrode active material layer slurry including the graphite onto the negative electrode current collector, and drying to obtain an unrolled negative electrode sheet;
[0107] The unrolled negative electrode sheet is rolled to obtain a negative electrode sheet.
[0108] The rolling operation can be performed by using a roller press according to a set compaction density. For example, a higher compaction density (such as 1.50 g / cm 3 ~1.90g / cm 3 ), rolling is performed under higher compaction conditions (such as setting the speed of the roller press to 10m / min to 40m / min and applying a pressure of 800MPa to 1500MPa to the graphite). Since the first structural stability coefficient X1 of the graphite in the embodiment of the present application is 0.9 to 1.8, it can meet the requirements of the above rolling operation on the stability of the graphite structure. Therefore, the above negative electrode sheet can provide a higher level of compaction density while ensuring the stability of the graphite structure, thereby helping the battery assembled using the negative electrode sheet to have a higher energy density.
[0109] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet to form a battery cell, and the electrolyte is injected into the battery cell. Among them, the negative electrode sheet comprises a negative electrode current collector, and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises the graphite as described in the first aspect, or the negative electrode active material layer comprises the graphite prepared by the preparation method as described in the second aspect.
[0110] Furthermore, the electrolyte includes: a lithium salt, an organic solvent and an additive, the additive includes a sulfonate compound, the mass fraction of the sulfonate compound in the electrolyte is W, 0.2%≤W / X1≤1.0%.
[0111] Controlling W / X1 within the above range is beneficial to further optimize the film-forming effect of the SEI film through the coordination of graphite and sulfonate compounds, and better reduce the initial efficiency loss and cycle performance of the battery.
[0112] First, in the process of making negative electrode sheets, graphite, as the negative electrode active material, will expose more active reaction sites after rolling. Sulfonate compounds have the characteristics of low film formation impedance, which makes it easier for them to generate low-impedance lithium sulfide and other components on the negative electrode surface during the battery cycle to form a corresponding protective film, preventing the active reaction sites of graphite from further reacting with the electrolyte.
[0113] Secondly, when the first structural stability coefficient X1 of graphite is in the range of 0.9 to 1.8, due to its good structural stability, the embedding and extraction of lithium ions during the charge and discharge process is not easy to cause the collapse and destruction of the graphite structure. At the same time, the graphite particles are more rounded, the film consumes less lithium ions, and the irreversible capacity is reduced, so the SEI film is more uniform and stable. Based on this structural feature of graphite, with the above-mentioned proportion of sulfonate compound additives, a uniform and dense SEI film can be formed in a shorter time. Therefore, the film-forming effect of the SEI film is further optimized by the combination of graphite and sulfonate compounds.
[0114] Further, W is 0.1% to 1.0%. Exemplarily, W is 0.1%, 0.2%, 0.3%, 0.5%, 0.7%, 0.8% or 1.0%.
[0115] Optionally, the sulfonate compound includes at least one of 1,3-propane sultone, 1,4-butane sultone or methylene methane disulfonate.
[0116] In a fifth aspect, an embodiment of the present application further provides an energy storage device 10, which includes the secondary battery described in the fourth aspect.
[0117] Taking electrochemical energy storage as an example, an embodiment of the present application provides an energy storage device 10, which has a group of chemical batteries in it. The chemical elements in the batteries are mainly used as energy storage media. The charging and discharging process is accompanied by chemical reactions or changes in the energy storage media. In simple terms, the electricity generated by wind and solar energy is stored in chemical batteries. When the use of external electricity reaches a peak, the stored electricity is released for use, or transferred to places where electricity is scarce for use.
[0118] The current energy storage (i.e., energy storage) application scenarios are relatively wide, including energy storage on the power generation side, energy storage on the grid side, and energy storage on the power consumption side. The corresponding types of energy storage devices 10 include:
[0119] (1) Large-scale energy storage power stations applied to wind power and photovoltaic power stations can help renewable energy generation meet grid connection requirements and improve the utilization rate of renewable energy. As a high-quality active / reactive regulating power source on the power supply side, energy storage power stations can achieve load matching of electric energy in time and space, enhance the ability to absorb renewable energy, reduce instantaneous power changes, reduce the impact on the power grid, improve the absorption of new energy generation, and are of great significance in power grid system backup, relieving peak load power supply pressure, and peak and frequency regulation.
[0120] (2) Energy storage containers used on the grid side mainly perform peak load regulation, frequency regulation, and grid congestion relief. They can achieve peak load shaving and valley filling of power loads, that is, charging the energy storage batteries when the power load is low and releasing the stored power during the peak load period, thereby achieving a balance between power production and consumption;
[0121] (3) Small energy storage cabinets used on the power consumption side, mainly for self-generation and self-use of electricity, peak-valley price difference arbitrage, capacity cost management and improving power supply reliability. According to different application scenarios, energy storage on the power consumption side can be divided into industrial and commercial energy storage cabinets, household energy storage devices, energy storage charging piles, etc., which are generally used in conjunction with distributed photovoltaics. Industrial and commercial users can use energy storage for valley-peak price difference arbitrage and capacity cost management. In the power market that implements peak-valley electricity prices, by charging the energy storage system 100 when the electricity price is low and discharging the energy storage system 100 when the electricity price is high, peak-valley electricity price difference arbitrage is achieved to reduce electricity costs. In addition, industrial enterprises that are subject to two-part electricity prices can use the energy storage system 100 to store energy during low electricity consumption and discharge it during peak load, thereby reducing peak power and the maximum demand reported, and achieving the purpose of reducing capacity electricity charges. Household photovoltaic storage can improve the level of self-generation and self-use of electricity. Due to high electricity prices and poor power supply stability, the demand for household photovoltaic installations is driven. Considering that photovoltaic power is generated during the day, and users generally have higher loads at night, energy storage can be configured to better utilize photovoltaic power, improve the level of self-generation and self-use, and reduce electricity costs. In addition, communication base stations, data centers and other fields need to configure energy storage for backup power.
[0122] See also Figure 1 , Figure 1 This is a structural diagram of a household energy storage system 101 of an embodiment of the present application. The present application provides a household energy storage system 101, which includes an electric energy conversion device 20 (photovoltaic panel), a first user load 30 (street lamp), a second user load 40 (such as air conditioners and other household appliances), and an energy storage device 10. The energy storage device 10 is a small energy storage box that can be mounted on an outdoor wall by wall hanging. Specifically, the photovoltaic panel can convert solar energy into electric energy during the period of low electricity prices. The energy storage device 10 is used to store the electric energy and supply it to street lamps and household appliances for use during peak electricity prices, or to supply power when the power grid is out of power / power outage.
[0123] See also Figure 2 , Figure 2 is a schematic diagram of the structure of a commercial energy storage system 102 according to an embodiment of the present application, and the present application Figure 2 The embodiment is described by taking the shared energy storage scenario on the power generation / distribution side as an example, and the energy storage device 10 of the present application is not limited to the energy storage scenario on the power generation / distribution side.
[0124] The present application provides a commercial energy storage system 102, which includes: a high-voltage cable 50, a first power conversion device 60, a second power conversion device 70 and an energy storage device 10 provided in the present application. In the case of power generation, the first power conversion device 60 and the second power conversion device 70 are used to convert other forms of energy into electric energy, connect to the high-voltage cable and supply it to the power distribution network for use. When the power load is low and the first power conversion device 60 and the second power conversion device 70 generate excess power, the excess power is stored in the energy storage device 10, reducing the wind and light abandonment rates and improving the problem of new energy power generation and consumption; when the power load is high, the power grid issues an instruction to use the power stored in the energy storage device 10 in conjunction with the high-voltage cable 50 to transmit the power to the power consumption side in a grid-connected mode, providing peak-shaving, frequency regulation, standby and other services for the operation of the power grid, giving full play to the role of the power grid in peak-shaving, promoting the peak-shaving and valley-filling of the power grid, and alleviating the power supply pressure of the power grid.
[0125] Optionally, the first electric energy conversion device 60 and the second electric energy conversion device 70 can convert at least one of solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.
[0126] The number of energy storage devices 10 can be multiple, and multiple energy storage devices 10 are connected in series or in parallel. Multiple energy storage devices 10 are supported and electrically connected by isolation plates (not shown). In this embodiment, "multiple" refers to two or more. An energy storage box can also be provided outside the energy storage device 10 to accommodate the energy storage device 10.
[0127] Optionally, the energy storage device 10 may include but is not limited to a battery module, a battery pack, a battery system, etc. The actual application form of the energy storage device 10 provided in the embodiment of the present application may be but is not limited to the listed products, and may also be other application forms. The embodiment of the present application does not strictly limit the application form of the energy storage device 10. The embodiment of the present application only takes the energy storage device 10 as a multi-core battery as an example for explanation. When the energy storage device 10 includes the single cell, the single cell may be at least one of a cylindrical battery, a square battery, etc.
[0128] The solution of the present application will be further introduced below in conjunction with specific embodiments and experimental data.
[0129] Example 1
[0130] <Graphite>
[0131] The graphite of this embodiment is prepared by the following method:
[0132] The petroleum coke is roughly crushed and ground for 1 hour to 5 hours to obtain a coarse material having a coarse material median particle size Dv0';
[0133] The coarse material is finely crushed with a power of 10 Hz to 50 Hz to obtain aggregate, and the aggregate has a median particle size Dv0;
[0134] Using asphalt as an additive to granulate aggregate to obtain a first material, the first material having a first median particle size Dv1; wherein the softening point of the asphalt is 200° C. to 250° C., and the amount of asphalt added is 0.01wt% to 5wt%;
[0135] The first material is shaped to obtain a second material, wherein the second material has a second median particle size Dv2, and the tap density of the second material is ≥0.5 g / cm 3 ;
[0136] The second material is pre-carbonized to obtain a third material, and the tap density of the third material is ≥0.7g / cm 3 ; Among them, the temperature of the pre-carbonization treatment is 700℃~1500℃, and the treatment time is 8h~60h;
[0137] The third material is graphitized to obtain a fourth material, and the tap density of the fourth material is ≥0.8g / cm 3 ; Among them, the Acheson furnace is used for graphitization treatment, the power of graphitization treatment is ≥500kW, the temperature of graphitization treatment is 2000℃~3000℃, and the insulation time is 12h~24h;
[0138] Graphite was obtained by sieving.
[0139] The median particle size and graphite parameters after each step are shown in Tables 1 and 2 below.
[0140] <Battery Assembly>
[0141] Preparation of positive electrode sheets: lithium iron phosphate, conductive agent acetylene black, and binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone solvent in a weight ratio of 96:2:2 and mixed evenly to obtain a positive electrode slurry with a solid content of 60wt%, and the positive electrode slurry is evenly coated on the positive electrode collector aluminum foil; after drying and cold pressing, a positive electrode sheet is obtained.
[0142] Preparation of negative electrode sheet: disperse graphite, conductive agent, sodium carboxymethyl cellulose and styrene-butadiene rubber in deionized water at a mass ratio of 96:1:1:2 and mix evenly to obtain a negative electrode slurry with a solid content of 50wt%; use a die head extrusion coater to coat the negative electrode slurry on the negative electrode collector and dry it to obtain an unrolled negative electrode sheet; use a roller press to roll the unrolled negative electrode sheet according to the set compaction density to obtain a negative electrode sheet. Among them, the graphite is the graphite prepared as described above; the rolling conditions of the roller press include: rolling at a speed of 10m / min to 40m / min and applying a pressure of 800MPa to 1500MPa.
[0143] Diaphragm: Made of PP (Polypropylene) porous polymer film.
[0144] Preparation of electrolyte: In an argon atmosphere glove box with a moisture content of ≤1ppm, ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed in a volume ratio of 3:7 to obtain a mixed solvent, and then dry lithium salt LiPF6 was added thereto to prepare an electrolyte with a concentration of 1 mol / L.
[0145] Assembly of secondary batteries: stack the above-mentioned positive electrode sheets, separators, and negative electrode sheets in order, so that the separator is located in the middle of the positive electrode sheets and the negative electrode sheets to separate the positive electrode sheets and the negative electrode sheets, and obtain bare cells after winding. After connecting the electrode ears, assemble the cells into outer packaging, inject electrolyte, and then encapsulate, let stand, form, shape, and perform capacity testing on the cells to finally prepare secondary batteries.
[0146] Embodiment 2 to Embodiment 3
[0147] The difference from Example 1 is that the graphite preparation process is adjusted to obtain different median particle sizes and graphite parameters of the materials after treatment in each step.
[0148] Embodiment 4 to Embodiment 7
[0149] The difference from Example 1 to Example 3 is that 1,3-propane sultone is further added to the electrolyte, and the mass fraction of 1,3-propane sultone in the electrolyte is W.
[0150] Embodiment 8~embodiment 10
[0151] The difference from Example 1 is that the graphite preparation process is adjusted to obtain different median particle sizes and graphite parameters of the materials after treatment in each step.
[0152] Embodiment 11
[0153] The difference from Example 1 is that the raw coke in this example is needle coke, and 1,4-butane sultone is also added to the electrolyte.
[0154] Comparative Example 1 to Comparative Example 2
[0155] The difference from Example 1 is that the graphite preparation process is adjusted to obtain different median particle sizes and graphite parameters of the materials after treatment in each step.
[0156] Comparative Example 3 to Comparative Example 4
[0157] The difference from Comparative Example 1 and Comparative Example 2 is that 1,3-propane sultone is further added into the electrolyte, and the mass fraction of 1,3-propane sultone in the electrolyte is W.
[0158] <Test>
[0159] (1) Particle size test
[0160] The particle size was measured using a laser diffraction particle size distribution measuring instrument (Malvern Mastersizer 3000) according to the particle size distribution laser diffraction method GB / T19077-2016. The particle size of graphite before and after rolling and the particle size of materials in each step of the graphite preparation process were measured using this method.
[0161] Among them, the graphite after rolling can be obtained as a sample to be tested by the following method: take the secondary battery of the above embodiment and comparative example in a fully discharged state (discharged to 2.0V), disassemble it, and take out the negative electrode sheet; soak 30g of the negative electrode sheet in 200mL pure water, stir it slightly for 1 minute, ensure that the negative electrode active material on the surface of the negative electrode current collector copper foil is completely removed, take out the copper foil, stir the solution for 30 minutes, ensure that the negative electrode active material is completely dispersed, and there are no agglomerated particles visible to the naked eye inside; let it stand for 6 hours, so that most of the solid matter is precipitated at the bottom of the container, and pour out the upper solution; add 200mL of water again, stir for 30 minutes, and pour out the solution after standing for 6 hours, repeat the above steps 3 times, and place the lower precipitate in an oven above 60°C for 6h until it is dried. Grind the block precipitate with a mortar for more than 15 minutes until there are no obvious agglomerates in it, and obtain a negative active material as a uniform powder.
[0162] The results are shown in Tables 1 and 2.
[0163] Table 1: Median particle size after each step of preparing graphite in the examples and comparative examples
[0164]
[0165]
[0166] Table 2: Structural stability coefficient of graphite in examples and comparative examples
[0167]
[0168] (2) Compacted density
[0169] Take 1g of graphite powder and add it to a mold with a diameter of 13mm. Put the mold into a press, pre-press at 30KN for 30s and then release the pressure. Then gradually apply pressure from 5KN to 50KN, maintain the pressure for 10s and release the pressure. Measure the mass and volume of the pressed cylinder. Compacted density = sample mass / sample volume.
[0170] (3) Tap density
[0171] The prepared sample is placed in a graduated cylinder and the graduated cylinder is fixed on a mechanical vibration device (instrument model Dandong Better BT-313). The vibration motor drives the mechanical vibration device to vibrate vertically up and down. The graduated cylinder containing the sample vibrates rhythmically with the mechanical vibration device. When the number of vibrations reaches the set number, the mechanical vibration device stops vibrating and the volume of the graduated cylinder is read. According to the definition of density: mass divided by volume, the tap density of the positive electrode active material / negative electrode active material after tapping is calculated.
[0172] (4) Specific surface area
[0173] Refer to GB / T 19587-2017 and use nitrogen adsorption specific surface area analysis test method.
[0174] (5) Gram capacity
[0175] The above-mentioned negative electrode plate and separator, metal lithium disc and electrolyte were assembled into CR 2032 button cells, and the assembled button cells were tested on the test system using the following test method: ① After the button cell was allowed to stand for 4 hours, it was discharged at a constant current of 0.1C to 0.005V and allowed to stand for 10 minutes; ② Then it was discharged at a current of 0.05mA to 0.005V and allowed to stand for 10 minutes; ③ Then it was discharged at a current of 0.01mA to 0.005V and allowed to stand for 10 minutes; ④ The battery was charged to 2V at a current density of 0.1C, and the gram capacity obtained in the final charging process was used as the gram capacity of the negative electrode.
[0176] (6) Battery cycle performance test
[0177] The secondary batteries of the examples and comparative examples were repeatedly charged and discharged by the following steps, and the discharge capacity retention ratios of the secondary batteries were calculated.
[0178] First, in an environment of 25°C, the first charge and discharge were carried out. Constant-power charging was performed at a charging power of 0.5P until the upper limit voltage of 3.65V was reached, and then constant-voltage charging was performed. Then, constant-power discharge was performed at a discharge power of 0.5P until the final voltage was 2.5V. This was repeated twice, and the discharge capacity of the second cycle was recorded. Then, 300 charge and discharge cycles were performed, and the discharge capacity of the 300th cycle was recorded.
[0179] Capacity retention rate after 300 cycles=(discharge capacity at the 300th cycle / discharge capacity at the second cycle)×100%.
[0180] The results are shown in Table 3 below.
[0181] Table 3: Graphite and battery performance of examples and comparative examples
[0182]
[0183] By comparing Examples 1 to 3 and Comparative Examples 1 to 2, it can be seen that when the first structural stability coefficient of graphite is in the range of 0.9 to 1.8, the battery using the graphite as the negative electrode active material has better cycle performance.
[0184] By comparing Examples 1 to 3 and Examples 4 to 7, it can be seen that when the first structural stability coefficient of graphite meets the range of 0.9 to 1.8, when sulfonate compounds are added to the electrolyte of the battery, it is beneficial to further improve the cycle performance of the battery. Among them, by comparing Examples 4 and 5, it can be seen that when the same graphite and different amounts of sulfonate compounds are used in the battery, the increase in the amount of sulfonate is beneficial to the improvement of the battery cycle performance. In addition, by further comparing Examples 4 to 7 and Comparative Examples 1 to Comparative Examples 4, it can be seen that when W / X1 is controlled within 0.2% to 1.0%, it is more conducive to the improvement of battery performance.
[0185] Comparing Examples 1 to 3 and Examples 8 to 10, it can be seen that the battery cycle performance of Examples 1 to 3 is better. It can be seen that when graphite satisfies the first stability coefficient of 0.9 to 1.8 and the second stability coefficient of 0.95 to 2 at the same time, it is beneficial to further improve the cycle performance of the battery.
[0186] The technical solutions disclosed in the embodiments of the present invention are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the technical solutions and core ideas of the present invention. At the same time, for those skilled in the art, according to the ideas of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A graphite, characterized in that: The graphite has a first structural stability coefficient X1, wherein X1 is (Dv90-Dv50) / (Dv90'-Dv50'), 0.90≤X1≤1.80; Among them, Dv90 is the particle size corresponding to 90% of the cumulative volume percentage of the graphite before rolling, Dv50 is the particle size corresponding to 50% of the cumulative volume percentage of the graphite before rolling, Dv90' is the particle size corresponding to 90% of the cumulative volume percentage of the graphite after rolling, and Dv50' is the particle size corresponding to 90% of the cumulative volume percentage of the graphite after rolling.
2. The graphite according to claim 1, characterized in that The rolling conditions include: applying a pressure of 800MPa to 1500MPa to the graphite at a rotation speed of 10m / min to 40m / min for rolling; and / or, The compacted density of the graphite is 1.50 g / cm 3 ~1.90g / cm 3 .
3. The graphite according to claim 1, characterized in that 17μm≤Dv90≤26μm; and / or, 10μm≤Dv50≤15.5μm; and / or, 17μm≤Dv90'≤25μm; and / or, 9.5μm≤Dv50'≤15μm.
4. The graphite according to claim 1, characterized in that The graphite also has a second structural stability coefficient X2, wherein X2 is (Dv90-Dv10) / (Dv90'-Dv10'), 0.95≤X2≤2; Wherein, Dv10 is the particle size corresponding to 10% of the cumulative volume percentage of the graphite before rolling, and Dv10' is the particle size corresponding to 10% of the cumulative volume percentage of the graphite after rolling.
5. The graphite according to claim 4, characterized in that 5μm≤Dv10≤9.5μm; and / or, 4μm≤Dv10'≤7.5μm.
6. The graphite according to any one of claims 1 to 5, characterized in that The tap density of the graphite is 1.0 g / cm 3 ~1.2g / cm 3 and / or, The specific surface area of the graphite is 1.1 m 2 / g~1.6m 2 / g; and / or, The gram capacity of the graphite is 340 mAh / g to 370 mAh / g.
7. A method for preparing graphite according to any one of claims 1 to 6, characterized in that: The method for preparing the graphite comprises the following steps: Crushing the raw coke to obtain aggregate, wherein the aggregate has a median particle size Dv0 of 6.0 μm to 9.0 μm; Granulating the aggregate to obtain a first material, wherein the first material has a first median particle size Dv1, 1.7≤Dv1 / Dv0≤2.6; The first material is shaped to obtain a second material, wherein the second material has a second median particle size Dv2, 1.5≤Dv2 / Dv0≤1.8; Pre-carbonizing the second material to obtain a third material; Graphitizing the third material to obtain a fourth material; The graphite is obtained by sieving.
8. The method for preparing graphite according to claim 7, characterized in that: Dv1 is 10.0 μm to 22.0 μm; and / or, Dv2 is 11.0 μm to 16.0 μm; and / or The tap density of the second material is ≥0.5g / cm 3 and / or, The tap density of the third material is ≥0.7g / cm 3 and / or, The tap density of the fourth material is ≥0.8g / cm 3 .
9. The method for preparing graphite according to claim 7, characterized in that: The step of crushing the raw coke to obtain aggregate comprises: The raw coke is coarsely crushed to obtain a coarse material, wherein the coarse material has a coarse material median particle size Dv0'; The coarse material is finely crushed to obtain the aggregate, 2.1≤Dv0' / Dv0≤2.8, and Dv0' is 13.0μm to 25.0μm.
10. A negative electrode plate, characterized in that: The negative electrode plate comprises: Anode current collector; A negative electrode active material layer is provided on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the graphite as claimed in any one of claims 1 to 6, or the negative electrode active material layer comprises graphite obtained by the method for preparing graphite as claimed in any one of claims 7 to 9.
11. A secondary battery, characterized in that: The secondary battery comprises: a positive electrode sheet, a negative electrode sheet as claimed in claim 10, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet to form a battery cell, and the electrolyte is injected into the battery cell.
12. The secondary battery according to claim 11, characterized in that: The electrolyte includes: lithium salt, organic solvent and additives, the additives include sulfonate compounds, the mass fraction of the sulfonate compounds in the electrolyte is W, 0.2%≤W / X1≤1.0%.
13. An energy storage device, characterized in that: The energy storage device comprises the secondary battery according to any one of claims 11 to 12.
Citation Information
Cited By
Graphite and preparation method thereof, negative electrode plate, secondary battery, and energy storage device
WO2026153408A1